Improved learning accessibility and professionalism of teachers in remote areas through mentoring development of teaching materials based on Augmented Reality - Sri Suryanti; Deni Sutaji; Yudhi Arifani; Muyasaroh Muyasaroh; Muhammad Zamzamy (OJS Universitas Muhammadiyah Gresik, 2020)
The problem that underlies the Augmented Reality-based teaching material development assistance program for teachers in remote areas is located in the gap in the progress of the quality of education between remote and urban areas caused by demanding access to cities, and the lack of knowledge and understanding of teachers in developing materials innovative teaching by utilizing current technological advancements. Community service activities aim to produce innovative teaching materials based on Augmented Reality at Muhammadiyah 4 Daun Vocational School and MTs Muhammadiyah 5 Daun Sangkapura, Bawean Island. Bawean Island is located 80 miles or 135 km north of Java. The geographical location and transportation conditions connecting Bawean and Gresik islands are the main obstacles for teachers on Bawean island to follow the development of science and technology which results in the low quality of the learning process so that it lags behind the development of information technology. Form of implementation of the program as a realization troubleshooting manifest in periodic and scheduled activities through a strengthening phase followed the concept of mobile learning needs analysis workshop, workshop material development, and implementation with the assistance of a team of stewards and continued application independently by the school in the implementation phase of using the steps Lesson Study as much as two cycles. The method used in the implementation of this activity is the method of discussion, workshops, and direct practice in class. Increased knowledge and ability of teachers teaching materials related to the development of innovative Augmented Reality-based and capable of producing the best practices in the implementation report the development of innovative teaching materials based Augmented Reality in learning in SMK Muhammadiyah 4 Daun and MTs Muhammadiyah 5 Daun Sangkapura, Bawean